A Literasi dan Numerasi dengan Media Kreatif 3 Dimensi (3D) di Yayasan Uswatun Hasanah Bontang - Zaini Zaini; Akbar Akbar; Abadi Nugroho (Abdimas Universal, 2023)
Yayasan Uswatun Hasanah Bontang as a partner in Community Service Program strives to implement literacy and numeracy programs. These efforts are not optimal because practically literacy and numeracy are measured by giving students assignments to read and count. Limited media to carry out good practices regarding literacy and numeracy influences its implementation. As an effort to provide the solution toward the problems, the implementor team of community service carried out: synchronizing the problems and the solutions, promoting the good literacy and numeracy practices, presenting workshop and training in making and using media of literacy and numeracy, and assisting in making creative media for literacy and numeracy, while the needed data is questionnaire of satisfaction level of the partners regarding this implementation of the program. The results of the program are the partner get deeper knowledge in designing and using literacy and numeracy media, the partners are happy for having literacy and numeracy media, and they hope that there will be follow-up program or cooperation in communicating the implementation of school literacy and numeracy.